Association Between Severity of Depression and Cardiac Risk Factors Among Women Referred to a Cardiac Rehabilitation and Prevention Clinic. Issue 5 (September 2018) - Bhardwaj, Meena; Price, Jennifer; Landry, Mireille; Harvey, Paula; Hensel, Jennifer M.
Abstract : Purpose: Depression comorbid with cardiovascular disease is associated with higher rates of morbidity and mortality, with studies suggesting that this is especially true among women. This study examined depressive symptoms and their relationship to cardiac risk factors among women referred to a women's cardiac rehabilitation and primary prevention program. Methods: A secondary analysis of data collected between 2004 and 2014 for 1075 women who completed a baseline assessment at the Women's Cardiovascular Health Initiative, a women-only cardiac rehabilitation and prevention program in Toronto, Canada. Descriptive statistics for sociodemographic variables, quality of life (SF-36), and cardiac risk factors were stratified by depression symptom severity using cutoff scores from the Beck Depression Inventory—2nd version (BDI-II) and compared with analysis of variance and χ 2 statistics. Prevalence of antidepressant use among those with moderate to high depressive symptoms was assessed as an indicator of under- or untreated depression. Results: Overall, 38.6% of women scored above the BDI-II cutoff for depression; 23.6% in the moderate or severe range. Socioeconomic status and quality of life decreased with increasing depression severity. Body mass index increased with depressive severity ( P < .001), as did the percentage of individuals with below target age predicted fitness ( P < .001). Only 39.0% of women in the moderate and severe BDI-II groups were taking antidepressants. Conclusion: In this sample, we found a significant prevalence of untreated and undertreated depressive symptoms among women with, or at high risk of developing, cardiovascular disease. Additional strategies are needed to identify these patients early and link them to appropriate treatment. Abstract : This study examined depressive symptoms in relationship to cardiac risk factors among women referred to a women-only cardiac rehabilitation and primary prevention program. The proportion of women on antidepressant treatment was also assessed. Results showed that there is an increased need to identify depression and provide treatment in this population.